PENGEMBANGAN DAN KEBUTUHAN INVESTASI SEKTOR AIR BERSIH DI JAWA TIMUR - Iwan Nugroho (Badan Penelitian dan Pengembangan Provinsi Jawa Timur, 2007)
This research aimed to implement demand approach on water supply development in East Java Province. Data collecting in conducted through field and institutional survey to obtain actual and behavioral variables. System analysis is aperated to project the water supply development dynamically, during 1993 to 2010 periods. Study involved variables and equation model in four subsystem, i.e. (i) final demand and regional GDP, (ii) production and investment, (iii) population and household, and (iv) surabaya’s raw water. Result of research showed that water supply development based on demand approach succeded to create significant incentive through water price and management improvement and willingness to pay promotion, succeeded to create a significant incentive for the water supply development. The policies of price growth 2 percent, gradual decreasing of unaccounted for water into 30 percent, and decreasing water connection fee have produced water suplly performance as follows : water service ratio of 43.5 percent, production capacity of 31 m3 per second, 5-years investment need of 1.38 trilions rupiahs and return on investment of 30 percent. Those investment come from 27 percent governance loan, 30 percent commercial loan and 12 percent equity.Private sector participation in water supply sector is a key word for improving efficiency and management, decreasing unaccounted for water, improving the servece ratio and creating investment.